Mimicking Melanopsin Behavior with Integrated Photoregulated Memory - Kumar, Mohit; Seo, Hyungtak (Advanced Optical Materials, 2021)
Melanopsin is an essential element in the human eye, sensing optical light, indeed beyond the function of rods and cones, and contributing largely to non-image-forming functions like learning behavior, emotions, and maintaining sun cycle. Mimicking melanopsin behavior using an optoelectronic device could be an essential step toward the advancement of future technologies, including data storage applications and artificial vision. This research proposes and illustrates the mimicking of the primitive functions of melanopsin in a manner very similar to the human eye retina by using an integrated Schottky photodetector and an HfO2-based memory device. Particularly, current–voltage curves show nominal hysteresis loop opening under dark conditions, whereas stable analog hysteresis loops form with light illumination, which is regulated progressively by increasing the intensity. Based on photoconductive atomic force microscopy and charge transport measurements, the charge trapping/detrapping is estimated to be associated with the light-regulated hysteresis loop opening. Specifically, versatile synaptic functions are stimulated artificially with an optical pulse, which is sustained over a long period of time even after removing the light, indeed very similar to melanopsin behavior. The optically regulated properties described herein pave the way for the development of artificial optoelectronic melanopsin, artificial biological electronics, soft robotics, and data storage applications.
Keywords: Artificial synapse; Conductive atomic force microscopy; Data storage applications; Essential elements; Human eye; Integrated schottky photodetector; Melanopsin; Optical light; Photoregulated memory; Schottky photodetectors; artificial synapses; conductive atomic force microscopy; integrated Schottky photodetectors; melanopsin; photoregulated memory